ANALISIS KESULITAN BELAJAR SISWA KELAS XI PADA MATERI MATRIKS DITINJAU DARI KEMAMPUAN KOMUNIKASI MATEMATIS SMK BINA INSAN BANGSA - Dea Siti Mutmainah; Putri Chania Sari (Departement of Mathematics Education, 2019)
The purpose of this study was to describe the learning difficulties of mathematics experienced by students of class XI Vocational School in terms of mathematical communication skills. This type of research is descriptive with a qualitative approach. The subjects in this study were 20 students pleasure XI Bina Insan Bangsa (BIB) Vocational School Ngamprah from the Department of Motorcycle Engineering (TSM) and Online and Marketing Business (BDPMS). Data collection techniques in this study used observation, tests and interviews, while data analysis techniques in this study were data collection, data processing, data presentation and conclusion drawing. So the conclusions that can be drawn from this study are that students' learning difficulties in mathematics are; difficulty of concepts and verbal difficulties. The causes of the difficulties experienced by students are among others due to the low mathematical communication skills of students.